Hak Atas Keterlupaan (Right to be Forgotten) dan Paradoks Keabadian Data: Tinjauan Filsafat Hukum Tentang Kedaulatan Individu di Ruang Siber - Zulfaidah, Rena; Saepullah, Usep (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This article profoundly examines the philosophical conflict between the Right to Be Forgotten (RTBF) and the phenomenon of the Paradox of Data Immortality characterizing the digital age. Employing normative legal research with conceptual and philosophical approaches, this study aims to reconstruct the concept of individual sovereignty threatened by permanent data footprints. Amidst a system ensuring perfect recall, individual sovereignty has transformed from physical autonomy to digital narrative autonomy; the right to control one's self-representation in the cyber public sphere. The RTBF, strengthened by jurisprudence such as the Google Spain ruling and Indonesia’s Law No. 27/2022 on Personal Data Protection, is asserted as an instrument to restore human dignity and the individual's freedom to change. However, its implementation faces serious philosophical challenges: the balancing test between the individual's right and public interest, particularly freedom of expression and collective memory. The analysis reveals that the balancing test must shift from merely assessing data relevance towards considering the magnitude of prejudice suffered by the individual. Prescriptive recommendations include establishing an Independent Digital Ethics Commission to ensure RTBF decisions are grounded in deep ethical considerations, maintaining that forgetting does not entail social amnesia.